Effectiveness of health teaching programme on knowledge and attitude regarding exclusive breastfeeding among primigravida attending Dhiraj hospital, Piparia Vadodara - H. N., Ravindra; R. Waghmare, Priyanka (International Journal of Nursing Research, 2023)
Exclusive breastfeeding is the unequal way to providing ideal food for the healthy and proper development of the newborn. Aim: “effectiveness of health teaching programme on knowledge and attitude regarding exclusive breastfeeding among primigravida attending dhiraj hospital, piparia vadodara”. Material and method: an evaluative research approach with pre-experimental one group pre-test-post-test design is used; nonprobability convenience sampling is used to collect the 60 samples of primigravida mother and data collected by administering the structured questionnaire and likert scale. Data were analyzed by using descriptive and interferential statistics such as standard deviation, chi- test, and paired „t‟ test. Result: the mean post-test knowledge score 22.28 ±1.94 was higher than the mean pre-test score 9.85 ±2.48 and the obtained “t” test value 30.48 (df =59) is significant at 0.05 level. Whereas, the mean post-test attitude score 50.26 ±3.82 was higher than the mean pre-test score 28.83 ±6.90 and the obtained‟ test value 18.47 (df=59) shows significant at 0.05 level, this finding demonstrates health teaching programme is effective. The analysis of the association between a demographic variable and pretest knowledge score was significantly associated with age, education, trimester and other variables were not associated. However, the association between a demographic variable and pre-test attitude score was significantly associated with age, education and others were not significant. \Conclusion: the study finding revealed that health teaching programme is effective to improve the knowledge and attitude regarding exclusive breastfeeding among primigravida mothers.